Multilingualism: Consequences for the Brain and Mind - Schwieter, John W. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Multilingualism: Consequences for brain and mind" brings together state-of-the art papers that examine the cognitive and neurological consequences of multilingualism through an exploration of how two or more languages are processed, represented, and/or controlled in one brain/mind.